Urbanism without effort : reconnecting with first principles of the city - Wolfe, Charles K. (Island Press, 2019)
How do you create inviting and authentic urban environments where people feel at home? Countless community engagement workshops, studies by consulting firms, and downtown revitalization campaigns have attempted to answer this age-old question. 0In 'Urbanism Without Effort', Chuck Wolfe argues that "unplanned" places can often teach us more about great placemaking than planned ones. From impromptu movie nights in a Seattle alley to the adapted reuse of Diocletian's Palace in Split, Croatia, Wolfe searches for the "first principles" of what makes humans feel happy and safe amid the hustle and bustle of urban life. He highlights the common elements of cities around the world that spontaneously bring people together: being inherently walkable, factors that contribute to safety at night, the importance of intersections and corners, and more. In this age of skyrocketing metropolitan growth, he argues, looking to the past might be our best approach to creating the urban future we dream about. 0A whirlwind global tour, 'Urbanism Without Effort' offers readers inspiration, historical context, and a better understanding of how an inviting urban environment is created